A Mediation Effect of Job Satisfaction and Affective Commitment in Relationship Between Passion and Work Intentions after Retirement. Issue 2 (June 2019) - Tarkar, Preeti; Dhamija, Somesh; Singh, Pawan
The aim of this study is to identify an intention towards work after retirement. This article examines the multilevel sequential mediating role of job satisfaction and affective commitment in the relationship between passion for work and intention towards work. This study has used 310 respondents retired from government jobs and data are collected through a well-administered questionnaire. Smart partial least square-structural equation modelling (SmartPLS-SEM) was used to analyse data. Path analysis of the structural model revealed that passion for work has a significant relationship with job satisfaction, affective commitment and intention towards work. The findings of the analysis show that the multilevel mediator model is significant ( β = 0.08, p < 0.05) at the 5 per cent level of significance. This study supports the satisfaction-commitment model and creates intention towards work after retirement. This research is unique in the sense that it relates passion for work and satisfaction-commitment model with the work intentions of the retired persons.